Consumer perceptions of sustainability towards ingredients, packaging, labelling, and storage conditions in milk, burger products, and plant-based alternatives: A study in Sweden and Italy - Helen Vaikma; Martin Kern; William Harwood; Valérie L. Almli (Future Foods)
Sustainability increasingly shapes consumer attitudes and purchasing decisions, but perceptions of what constitutes sustainability vary. This study, conducted in Sweden and Italy in 2022 with 600 respondents, examined sustainability in a multidimensional manner (across social, environmental, economic, and health dimensions) for burgers and milk. Using the Sustainability Dimensions Perception Scale (SDPS) and a Choice-Based Conjoint (CBC) analysis, the research found that the food ingredient’s origin (animal vs. plant) was the most important characteristic for defining a sustainable product, particularly for burgers. Plant-based options were associated with higher perceptions of social, environmental, and health dimensions in both dairy and burger categories. Packaging, labelling and storage conditions were generally perceived to be less important for sustainability perception, and associations with different sustainability dimensions depended on the specific product category (i.e. milk or burger). In addition, five consumer segments were identified in the dairy and burger categories: “Animal-based food”, “Local label”, “Label importance”, “Plant-based food”, and “Cardboard container”, each reflecting diverse priorities in sustainability. As a result, this study addressed the general sustainable attitudes and product-specific attitudes, building on a multidimensional framework. This study offered valuable insights for understanding consumer preferences and developing strategies to guide them toward more sustainable choices.